A escola normal de Uberaba (1881-1905): memória e cotidiano - Oliveira, André Luís (2018)
The present study aimed to investigate and analyze Normal School of Uberaba within its first period of existence, between 1881 and 1905. As main goals were set to recover the memory and daily life of this institution and to understand the reasons that led to city of Uberaba, in Minas Gerais state of Brazil, to be chosen as the first institution to train and certify teachers in Triângulo Mineiro region, one of the eight schools that emerged in Minas Gerais state between 1870 and 1883. The research hypothesis for this city to be chosen may be because of its economical development in a region that was being projected nationally at that moment.The present work was based on specialized literature and on the analysis and interpretation of primary sources, having as a methodological support for research and textual writing the new history. The examination of primary documents allowed the study to rescue aspects of a forgotten daily life, such as the fact that the society incarcerates its demented people in prisons, a drama lived by the professor and former director Antônio Mamede de Oliveira Coutinho. Furthermore the analysis of the researching sources pointed out issues related to the period of existence of the institution come to the fore, such as: the expansion and professionalization of the teaching profession, the initial process of gender inversion in the teaching profession, the beginnings of coeducation and the desire for its laicization manifested by some lenses attached to the local republican movement. In the perspective of evidencing facts related to the daily school life, the documents revealed the presence of a traditional teaching, which was focused on memorization and a curriculum that contemplated Catholic religious teaching, a common feature context of a society that lived under the rules of the union of church and State. Moreover it allowed us to raise the hypothesis that there was a doctrinal weight in the students' education that was linked to Catholicism. Further analysis of the documentation confirmed this hypothesis. On the other hand, some teachers were against the teaching of the catechism, in a proposal of secularization of the same, one of the motives defended by republicans. That one and other debates that took place at the national level were present inside the Normal School of Uberaba. The identification of these questions was one of the results that we considered relevant in our research. Among other results achieved, we highlight the recovery of unpublished documents, the fact that the school has contributed to the training of teachers for the regional magisterium, for the dissemination of literacy and for the expansion of the regional influence of Uberaba in the educational scenario in Minas Gerais.This study pointed out that there were situations of weaknesses that were erased by time, which were not recorded by the memorialist writers, such as the fact that the initial euphoria motivated by the institution's installation had overshadowed negative points, including a precarious infrastructure in terms of building and school resources. Another weakness was the lack of a proper place that accompanied the school's trajectory, leading us to see that it depended on the goodwill of local political leaders linked to the Liberal Party. These politicians took advantage of the situation to politically equip the establishment of education, assigning good part of its positions among coreligionists. In this perspective the school became an environment of political disputes, unchanged conjuncture with the advent of the Republic.This research concluded that being in the center of such disputes and living with diverse weaknesses were negative elements in the journey of the Normal School of Uberaba. Keywords: Normal School; Uberaba; Teachers training; Daily life; Precariousness.